Higher number of multidisciplinary tumor board meetings per case leads to improved clinical outcome - Freytag, Marius; Herrlinger, Ulrich; Hauser, Stefan; Bauernfeind, Franz G.; Gonzalez-Carmona, Maria A.; Landsberg, Jennifer; Buermann, Jens; Vatter, Hartmut; Holderried, Tobias; Send, Thorsten; Schumacher, Martin; Koscielny, Arne; et al. (BMC cancer, 2020)
Background This analysis aims at evaluating the impact of multidisciplinary tumor boards on clinical outcome of multiple tumor entities, the effect of the specific number of multidisciplinary tumor boards and potential differences between the tumor entities. Methods By a matched-pair analysis we compared the response to treatment, overall survival, relapse or disease free survival and progression free survival of patients whose cases were discussed in a tumor board meeting with patients whose cases were not. It was performed with patients registered in the cancer registry of the University of Bonn and diagnosed between 2010 and 2016. After the matching process with a pool of 7262 patients a total of 454 patients with 66 different tumor types were included in this study. Results First, patients with three or more multidisciplinary tumor board meetings in their history show a significantly better overall survival than patients with no tumor board meeting. Second, response to treatment, relapse free survival and time to progression were not found to be significantly different. Third, there was no significant difference for a specific tumor entity. Conclusion This study revealed a positive impact of a higher number of multidisciplinary tumor boards on the clinical outcome. Also, our analysis hints towards a positive effect of multidisciplinary tumor boards on overall survival.